Gut microbiota and thyroid diseases – summary of current knowledge - Aleksander Daniluk; Kaja Iwaniuk; Martyna Wojda; Magdalena Świstowska; Aleksandra Wielgosz (Quality in Sport, 2024)
Introduction and purpose: The gut microbiota is a diverse collection of microorganisms that coexist in the human intestine. Disorders in its structure leads to dysregulation of huge number of organs, including the thyroid. This review summarizes the latest findings regarding the links between gut microbiota and common thyroid diseases: Hashimoto's thyroiditis, Graves' disease and thyroid cancer.